Practical Electrical Engineering - Makarov, Sergey N.; Ludwig, Reinhold; Bitar, Stephen J. (Springer, 2016)
Electricity, Electric field intensity, Electric field, Electric field magnitude, Lines of force, Electric potential, Electric voltage, Line integral, Contour integral, Conservative field, Potential energy of the electric field, Voltage drop, Voltage difference, Ground reference, Neutral conductor, Common conductor, Voltage versus ground, Equipotential lines, Volumetric charge density, Surface charge density, Gauss’ theorem, Equipotential surface, Self-capacitance, Electrostatic discharge, Effect of electrostatic discharge on integrated circuits, Boundary element method, Electric current density, Material conductivity, Transmission line, Direct current (DC), Electric load, Ideal wire, Kirchhoff’s voltage law (KVL), Magnetic field, Magnetic-field intensity, Ampere’s law, Cross (vector) product, Poynting vector, Poynting theorem, Wireless communications, Wireless power transfer, Fluid mechanics analogy of an electric circuit, Hydraulic analogy of an electric circuit, Voltage source (hydraulic analogy), Resistance (hydraulic analogy), Current source (hydraulic analogy), Capacitance (hydraulic analogy), Inductance (hydraulic analogy), Electric transformer (hydraulic analogy), NMOS transistor (hydraulic analogy), Bipolar junction transistor (hydraulic analogy)